Pengaruh jenis kulit pisang dan variasi waktu fermentasi terhadap kelistrikan dari sel accu dengan menggunakan larutan kulit pisang (Effect of banana peel type and fermentation time variation on the electricity of battery cells using a banana peel solution) - Yasni Novi Hendri; - Gusnedi; - Ratnawulan (Department of Physics – Universitas Negeri Padang UNP, 2015)
One attempt to deal with the energy crisis is the search of alternative energy. Of organic materials as well as inorganic material potentially to serve as alternative energy. Among them, waste banana peels that can be used as a biobaterai. One way to make banana peels as the optimal biobaterai with he does study of electricity generated from biobaterai by making a banana peels as a solution of elektrolitnya using a container of accu. The purpose of this study was to investigate the influence of different types of banana peels and fermentation time variation against electricity from cells using aqueous acid to the skin of a banana. This research was conducted on variation of skin types of bananas (ambon, raja, kepok and mas) and variations of the fermentation time (48, 96, 144 and 189 hours). In this study obtained data current and voltage measurement results of accu by using a solution of banana peels. Based on data obtained optimal banana peels type to serve as biobaterai is ambon banana with the value of the voltage and the current volt 33.08 mA. The fermentation time for 192 hours has obtained value of current and voltage for aqueous banana peels ambon, kepok, King and mas in a row was 33.08 mA and 3.70 volt, 25 mA and 3.23 volt, 24.65 mA and 2.88 volt, and 24.26 mA and 3.02 volt. The length of time the fermentation lowers the pH value of the material. This is because the process of the activity of microorganisms in the materials that increased, so that the electron transfer process took place rapidly resulting in the voltage and current values are getting lar